PWE-130 Phenotype And Localisation Of Liver Infiltrating B Cell Subsets In Autoimmune And Inflammatory Liver Diseases. (9th June 2014) - Geh, D; Jeffery, H; Adams, DH; Oo, YH
Abstract : Introduction: B cells classically provide humoral immunity in the form of antibody production as part of the adaptive immune response. Regulatory and antigen presenting functions of B cells have been reported before and autoantibodies are associated with autoimmune liver diseases. B cell depletion in animal models of PBC has highlighted the regulatory roles of B cells in ameliorating disease. Some evidence of efficacy of anti-B cell therapy using rituximab in human autoimmune liver diseases further supports a role for B cells. Mature B cells (Bm) subpopulations had been described in Sjogren's syndrome. However, little is known about the localisation, subsets, phenotype and function of B cells in human liver diseases. Methods: In this study we characterised the frequencies of B cell subsets in the blood and liver of patients with inflammatory and autoimmune liver diseases. Results: Frequencies of naïve mature BM1 cells were reduced in the liver compared to blood (7.5% ± 2.3 vs. 20.2% ±2.8 p = 0.0022) and IgD neg CD27 neg subset was increased in diseased livers compared to diseased blood (22.9% ± 6.8 vs. 6.0% ± 1.1 p = 0.0013). B cells localise close to the bile ducts in PBC and reside around hepatocytes in AIH. Frequencies of regulatory B cells (CD19 pos CD24 hi CD38 hi ) were significantly reduced in diseased blood vs. control blood (1.8% ± 0.4 vs. 3.6% ± 0.5 p = 0.01) similar to recent observation in acute rheumatoid arthritis. However this population is increased in the diseased liver compared with blood (6.2% ± 0.07 vs. 1.8% ± 0.4 p = 0.007), suggesting enrichment of regulatory B cells within the inflamed liver. Liver infiltrating B cells were capable of IL-10 production. Conclusion: We have characterised for the first time the heterogeneity of B cell subsets and presence of regulatory B cells and IL-10 secreting B cells in human diseased livers. We showed that B cells reside close to bile ducts along with other immune cells; thus B cells may play a role in biliary pathology. Disclosure of Interest: None Declared.